The Effect of Cash On Delivery, Free Shipping Promos on Customer Reviews with Purchase Decisions as an Intervening Variable on the Shopee Marketplace Site in the Tangerang City Area - Alexander; Yanti Pusp Rini; Toni Yoyo (LPPM Universitas Buddhi Dharma, 2024)
This study examines and analyzes the influence of cash on delivery, free shipping promos, on customer reviews with purchase decisions as an intervening variable. The purpose of this study is to find the influence of each variable. The research method used a quantitative approach with a sample of 115 respondents. The analysis tool uses Smart-PLS. The results of this study show that cash on delivery has an effect on customer reviews explaining that cash on delivery has an effect on customer reviews seen from the significance level of 0.015<0.05 which means H1 is accepted. Cashon delivery has an effect on purchase decisions based on the results processed that the cash on delivery variable affects purchase decisions with a significance value of 0.000<0.005. Therefore, it can be concluded that H2 is accepted. Customerreviews have an effect on purchase decisions based on the results of the study that customer reviews have a significance value of 0.033<0.05, therefore it can be concluded that H3 is accepted. The freeshipping promo affects customerreviews explaining that the free shipping promo affects customer reviews with a significance level of 0.000<0.05 which means H4 is received. Customer reviews and free shipping promos are things to consider when buying goods online. The freeshipping promo has an effect on purchase decisions based on research that is processed that the variable of free shipping promo with a significance value of 0.130>0.05 which means H5. Cashon delivery affects customer reviews through purchase decision variables as intervening variables, based on research that the cash on delivery variable on customer reviews with a significance value of 0.010 which means H6 is accepted. The free shipping promoaffects customer reviews through the purchase decision variable as an intervening variable, based on the research that the free shipping promo variable on customer reviews with a significance value of 0.040 which means that H7 is accepted.